Mummy portraits: Investigating regional variations - Ragheb, Maryan Ragheb Sobhy (AUC Knowledge Fountain, 2016)
In Roman Egypt, a new form of funerary art known as "mummy portraits" emerged. As a development from the earlier funerary masks common in Pharaonic and Ptolemaic Egypt, mummy portraits, images of the deceased painted on wooden panels and inset into the mummy wrappings over the face, became a growing trend from the early 1st century AD and continued to be popular for the next 200 years. Even though scholars have adopted various approaches in studying mummy portraits stylistically in terms of hair, clothing, and jewelry styles for chronological sequencing, little stylistic analysis has been carried out to attribute specific portraits to specific sites using style of painting or panel shape as criteria. An exception is Lorelei Corcoran, who drew associations between the panel and the site to which it belongs, identifying arched panels with Hawara and angled ones with Er-Rubayat. These remarks may indicate that each site had a portrait-painting workshop, each with its own distinctive characteristics. This study analyzes portraits excavated from Hawara, Abusir el-Melek, Tebtunis, and Antinoopolis. These sites have been selected because they have yielded the highest numbers of excavated, and thus securely provenanced, portraits. These have been divided into two categories: the first consists of mummy portraits that are no longer attached to their mummies and the second includes those still in situ on the mummy. The variables examined are the material on which the portrait is painted, painting technique, panel shape, the presence of frames, the posture of the portrayed subject, presence of gilding, and areas gilded. For the second category, the decorative scheme of the mummy wrappings and the shape of the opening are added to the variables. The information has been entered into a database, and the results of the analysis provide a 'fingerprint' for each site. The 'fingerprints' can be used to tentatively assign portraits with unknown or uncertain provenance to specific sites, and thus has wide reaching implications to the study of Roman mummy portraits.